Sports Organizations as Complex Systems: Using Cognitive Work Analysis to Identify the Factors Influencing Performance in an Elite Netball Organization - Hulme, Adam; McLean, Scott; Read, Gemma J. M.; Dallat, Clare; Bedford, Anthony; Salmon, Paul M. (Frontiers in Sports and Active Living, 2019)
There is increasing interest in the adoption of a complex systems thinking approach when attempting to understand and optimize sports performance. Despite this, few studies have attempted to model elite sports organizations. The aim of this study was to use methods from the Cognitive Work Analysis (CWA) framework to develop a model of an elite netball organization and identify wider organizational functions and constraints influencing performance. Two phases of CWA were used: (i) Work Domain Analysis (WDA); and, (ii) Social Organization and Co-operation Analysis (SOCA). A WDA model of the elite netball organization was developed via subject matter expert (SME) workshops, and a SOCA was undertaken to identify the different functions, roles, and responsibilities of key actors within the organization. The findings identify various factors that influence performance. Functions that appear to provide a competitive edge are discussed, including a strong club ethos, a shared responsibility for performance, and a focus on player and staff health and well-being. Factors that potentially have a negative impact on performance include organizational priorities not related to playing netball, and additional coach and athlete roles beyond coaching, training, and playing. The implications for understanding and optimizing elite sports organizations are discussed.